Use of Banana Peel in the Development of a Less Flammable Polyester Composite - Ferdausee Rahman Anannya; Farhana Afroz; Golam Kibria; Md. Lutfor Rahman; Nasrin Jamine; Md. Arif Mahmud (Tekstilec, 2022)
This study attempted to produce a cheap polyester composite material using an agricultural waste banana peel in the structure. Banana fibre has been used in composites as reinforcements, but banana peel has never been used with polyester before. The possibility of improved thermal and flammability properties of a composite due to increased moisture in the structure, and the char-forming ability of the cellulosic part of banana peel or the production of highly flammable material due to the presence of carbohydrates in the structure were the assumptions. To tackle the second assumption, aluminium trihydrate (ATH) was added. The handmade composites showed a drastic drop in tensile strength from 38.02 MPa to 16.72 MPa due to a lack of chemical bonding between the constituents. The impact and flexural strength showed some improvement with the addition of banana peel, along with ATH, to record results of 10.92 kg/cm and 49 MPa, respectively, after the initial drop that occurred when only ATH was added. However, these results were still inferior to the properties of pure polyester. The results of flammability and thermal resistance matched the second assumption, as flame retardancy was kept under control by the presence of ATH. The absorbency properties remained almost unaffected.